2013
DOI: 10.1111/papt.12012
|View full text |Cite
|
Sign up to set email alerts
|

Anxious and avoidant attachment styles and indicators of recovery in schizophrenia: Associations with self‐esteem and hope

Abstract: If self-esteem and/or hopelessness are identified as a focus of treatment, focusing on attachment style may be an important treatment component. Therapist understanding of patients' attachment style may allow for a better understanding of resistance in the therapeutic relationship. Helping persons with schizophrenia to recognize and change how they tend to relate to others may promote gains in subjective elements of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 64 publications
0
11
1
1
Order By: Relevance
“…The current analysis found the greatest relationship between positive symptoms and anxious attachment style, which is in contrast to previous reviews that have more commonly reported a relationship between avoidant attachment style and increased symptom severity within psychosis populations (Berry et al, 2007b;. However, anxious attachment style has been linked to low self-esteem and a negative self-image in psychosis (Ringer, Buchanan, Olesek & Lysaker, 2014) Berry et al, 2007b) known to contribute to the positive symptoms of psychosis through the misappraisal of anomalous experiences (Garety, Kuipers, Fowler, Freeman & Bebbington, 2001). Additionally, positive symptoms could develop as a result of increased anxiety and poorer affect regulation in psychosis (Gumley & Schwannauer, 2006) as research in at risk groups has found high rates of interpersonal sensitivity and stress reactivity can predict positive symptoms, such as paranoia, in non-clinical and at-risk samples (Lataster, Valmaggia, Lardinois, van Os & Myin-Germeys, 2013;Masillo et al, 2012).…”
Section: Attachment Insecurity and Positive Symptoms Of Psychosiscontrasting
confidence: 99%
“…The current analysis found the greatest relationship between positive symptoms and anxious attachment style, which is in contrast to previous reviews that have more commonly reported a relationship between avoidant attachment style and increased symptom severity within psychosis populations (Berry et al, 2007b;. However, anxious attachment style has been linked to low self-esteem and a negative self-image in psychosis (Ringer, Buchanan, Olesek & Lysaker, 2014) Berry et al, 2007b) known to contribute to the positive symptoms of psychosis through the misappraisal of anomalous experiences (Garety, Kuipers, Fowler, Freeman & Bebbington, 2001). Additionally, positive symptoms could develop as a result of increased anxiety and poorer affect regulation in psychosis (Gumley & Schwannauer, 2006) as research in at risk groups has found high rates of interpersonal sensitivity and stress reactivity can predict positive symptoms, such as paranoia, in non-clinical and at-risk samples (Lataster, Valmaggia, Lardinois, van Os & Myin-Germeys, 2013;Masillo et al, 2012).…”
Section: Attachment Insecurity and Positive Symptoms Of Psychosiscontrasting
confidence: 99%
“…Thus, perceptions of support from friends or family may influence the recovery process differently (58). Another study found an association between interpersonal relationships, characterized by secure attachment, and participants' levels of hope and self-esteem, suggesting that secure attachments are related to recovery (62).…”
Section: Relationship With Significant Others (Friends/family)mentioning
confidence: 99%
“…Other studies similarly identified peer relationships as key to supporting recovery (61,72). Many studies described connecting to others, social functioning, and social relationships as important for recovering "coherence, " reducing isolation, making meaning of experiences, and instilling hope (35,58,62,82). One study, involving a group rehabilitation program, described a sense of belonging, or security, acceptance, and connection to others that fosters a feeling that one is a part of a stigma-free community as a mechanism of recovery (64).…”
Section: Relationship With the Broader Communitymentioning
confidence: 99%
“…Studies on patients diagnosed with psychosis have indicated that a diagnosis of psychotic disorders was associated with insecure states of mind in the adult attachment interview (AAI; Hesse, 1999 ) as compared with patients diagnosed with affective disorders ( Dozier et al, 1991 ). Insecure attachment was also related to paranoid thoughts among adolescents with early psychosis as compared with controls ( Korver-Nieberg et al, 2013 ) and with worsened indicators of recovery as compared with participants with HIV/AIDS who had no history of experiencing severe mental illness ( Ringer et al, 2013 ).…”
Section: Attachment and Thought Disorder Spectrummentioning
confidence: 99%